Effects of monochord music on heart rate variability and self-reports of relaxation in healthy adults - Gäbel, Christine; Koenig, Julian; Warth, Marco (Complementary medicine research, 2017)
Background: Music-based interventions are considered an effective and low-cost treatment option for stress-related symptoms. The present study aimed to examine the trajectories of the psychophysiological response in apparently healthy participants during a music-based relaxation intervention compared to a verbal relaxation exercise. Material and Methods: 70 participants were assigned to either receptive live music (experimental group) or a prerecorded verbal relaxation exercise (control group). Self-ratings of relaxation were assessed before and after each intervention on visual analogue scales and the Relaxation Inventory (RI). The heart rate variability (HRV) was continuously recorded throughout the sessions. Statistical analysis focused on HRV parameters indicative of parasympathetic cardiovascular outflow. Results: We found significant quadratic main effects for time on the mean R-R interval (heart rate), the high-frequency power of HRV (indicative of parasympathetic activity), and the self-ratings of relaxation in both groups. A significant group × time interaction was observed for the cognitive tension subscale of the RI Conclusions: Participants in both groups showed psychophysiological changes indicative of greater relaxation over the course of the interventions. However, differences between groups were only marginal. Music might be effective in relieving stress and promoting relaxation by altering the autonomic nervous system function. Future studies need to explore the long-term outcomes of such interventions.